General correlation between neonatal factors, primary and permanent tooth eruption and their interrelation in a population in german orthodontic practices - Stephan Christian Möhlhenrich; Volkan-Cem Korkmaz; Sachin Chhatwani; Gholamreza Danesh (BMC, 2023)
Abstract Background The purpose of the study was to determine the possible relationship between the eruption of primary and permanent teeth and neonatal factors in German children according to gender. Methods A cross-sectional survey study was performed in 10 German orthodontic practices. Using a questionnaire information about gender, time of birth (week of pregnancy), birth weight (g) and height (cm), and the age of first primary and first permanent tooth eruption (months/years) of 405 children (230 girls and 175 boys) were collected. A Mann-Whitney U-test was used for group comparisons, and correlations were verified using a Pearson test. Results No correlation was found between neonatal factors (time of birth, birth weight, and birth height) and primary tooth eruption for male participants. However, for females a low correlation was found between the eruption of the first primary tooth and birth weight (r = -0.18, CI: -0.30 to -0.042, p = 0.011) and birth height (r = -0.19, CI: -0.32 to -0.054, p = 0.006). No correlations between neonatal factors and the eruption of the first permanent tooth were found for either gender. A moderate correlation was found between the first primary and first permanent tooth eruption (females: r = 0.30, CI: 0.16 to 0.43, p < 0.001; males: r = 0.22, CI: 0.059 to 0.35, p = 0.008). Conclusions An earlier eruption of the primary teeth can be assumed with greater body weight and height at the time of birth for girls. For boys, the tendency is the opposite. However, there seems to be a catch-up growth effect due to the missing differences between both permanent tooth eruption times. Nevertheless, the first primary and the first permanent tooth eruption correlates in a German children population.